Forensic Science or Forensic Sciences? A conceptual analysis (Research, Society and Development, 2022)
Science and justice need to interact to resolve different situations. This interaction, however, needs to occur efficiently to avoid generating even more doubts. Scientific evaluation in the legal context must be understood and achieve its purpose. For this, much has been discussed about the nature and purpose of forensic scientific assessment. In this work, the aim was to evaluate what forensic science is and what is the conceptual alignment of this area of knowledge concerning the national and international scenarios. We performed a bibliographic review on the subject to understand the fundamental aspects of this theme. Conceptual studies on forensic science are practically non-existent in the national literature. Forensic science was contextualized in its multi, inter, and transdisciplinary aspects. The quantitative results of the bibliographic review showed the urgent need for developing the theme in the national scenario and its alignment with the world understanding. Historical aspects of the development of forensic science were used in the discussion about the conceptualization of the term. Yet, internationally there are constant efforts to define the purpose and scope of forensic science. The Sydney Declaration was launched recently as a guiding document. We concluded that discussion about the concept of forensic science must be constant to improve it at the national level and to align it with international thinking. Hopefully, this work will encourage the discussion of the topic, strengthening the development of forensic science and reinforcing its importance for the administration of justice.